The Syntactic Omission Applications In The Arabic Verbal Sentence In The Book Mukhtaṣar Fi Shawazh al-Quran By Ibn Khalawyh/ تطبيقات التوجيه بالحذف في الإسناد الفعلي في كتاب مُختصَر في شواذِّ القرآن لابن خالويه - Lubna Shakeel; Adham Hamawiya (Ijaz Arabi Journal of Arabic Learning, 2023)
Ibnu Khalawayh is considered one of the greatest linguists who contributed to the science of Quranic readings, especially the shazah readings. Among his contributions is the book “Mukhtasar Fi Shawaz il Quran.” The research explains the shazah readings within a grammatical context.  In view of the importance of the phenomenon of omission in the Qur’anic readings, the topic of omission in predicate structures was chosen to reveal their manifestations and aspects. The research  based on the descriptive analytical method concludes that the reason for Ibnu-Khalawayh's lack of fame in grammar was his new grammatical concept. He believed that language is taken by hearing (sama’), not by analogy (qiyas), and the predicate in the actual sentence if it is omitted, the appropriate verb in the sense is estimated, and omission of predicate is either to weaken, strengthen, or limit the event, or for the purpose of its mention before and the increase in shazah reading may be considered omitted in frequent reading, and vice versa. It is expected that this research will be useful to learners of the Arabic language in the context of developing their grammatical distinction and syntactic omission skills, as a modality of intellectual activity that requires the expansion of knowledge through both types of inference, i.e., analogy and induction.